Review Artikel: Analisis Kandungan Cemaran Logam Berat pada Ikan yang Berada di Sungai Indonesia - Yuni Lili Indriyani; Munir Alinu Mulki (Poltekkes Kemenkes Padang, 2024)
Fisheries production in Indonesia will reach 24.74 million tonnes in 2023 and will increase compared to 2022 which was only 22.26 million tonnes. Increased production is in line with increased consumption which cannot be separated from food safety problems, especially the problem of heavy metal contamination originating from domestic waste and factory waste. The purpose of this review article is to provide information for knowledge and awareness to the public regarding the fish they consume. This review was carried out using searches via Google Scholar and Researchgate published in the last 10 years (2014-2024). The total articles used were 11 scientific articles. The research results show that there is heavy metal contamination such as lead, mercury, cadmium, arsenic, copper, manganese, chrome, cobalt, argentum, zinc and tin at different levels in each location. The most heavy metal contamination is lead (Pb) with the highest level of 4,242 mg/kg in tilapia fish in the Tenggang River, Semarang at the location of the first testing station, namely the upstream area with coordinates 6°57'49.8